2022
DOI: 10.1016/j.ophtha.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Pharmacotherapies for Diabetic Macular Edema

Abstract: To review the evidence on the safety and efficacy of current anti-vascular endothelial growth factor (VEGF) and intravitreal corticosteroid pharmacotherapies for the treatment of diabetic macular edema (DME).Methods: Literature searches were last conducted on May 13, 2020, in the PubMed database with no date restrictions and limited to articles published in English. The combined searches yielded 230 citations, of which 108 were reviewed in full text. Of these, 31 were deemed appropriate for inclusion in this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The neuroretina's aberrant thickening due to fluid accumulation, frequently accompanied by macular cystoid edema, is the most common cause of vision loss in patients with DR [ 108 ]. Intravitreal injections of corticosteroids and anti-VEGF medications are effective treatments for DME [ 109 ]. One study showed that bevacizumab reduced VEGF and APN concentrations in patients with T2DM, with a corresponding improvement in visual function and no ocular or systemic side effects [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroretina's aberrant thickening due to fluid accumulation, frequently accompanied by macular cystoid edema, is the most common cause of vision loss in patients with DR [ 108 ]. Intravitreal injections of corticosteroids and anti-VEGF medications are effective treatments for DME [ 109 ]. One study showed that bevacizumab reduced VEGF and APN concentrations in patients with T2DM, with a corresponding improvement in visual function and no ocular or systemic side effects [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal dexamethasone implant (DEX-i) has proven to have a beneficial impact on both anatomic and functional clinical outcomes since it is capable of acting both on inflammatory and on vasogenic mediators [ 16 18 ]. Additionally, patients who did not adequately respond to anti‐VEGF treatment should be switched to DEX-i as soon as possible, and preferably after 3 doses of anti-VEGF [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Elevated levels of VEGF detected in the vitreous have been identified as the primary cause of cystic macular edema caused by DME and RVO, hence Ranibizumab and Aflibercept are also widely used in DME and RVO. [12,13] Corneal endothelial cells are hexagonal, and their Na-K pump can effectively maintain the transparency of the cornea. [14] The regenerative capacity of corneal endothelial cells is extremely limited and they cannot be regenerated once damaged, but can be potentially replaced by expansion of surrounding normal endothelial cells, fusion between cells, or rare cell division.…”
Section: Discussionmentioning
confidence: 99%